Bishops, clerks, and diocesan governance in thirteenth-century England reward and punishment - Burger, Michael, 1962- (New York : Cambridge University Press, 2012)
"This book investigates how bishops deployed reward and punishment to control their administrative subordinates in thirteenth-century England. Bishops had few effective avenues available to them for disciplining their clerks and rarely pursued them, preferring to secure their service and loyalty through rewards. The chief reward was the benefice, often granted for life. Episcopal administrators' security of tenure in these benefices, however, made them free agents, allowing them to transfer from diocese to diocese or even leave administration altogether; they did not constitute a standing episcopal civil service. This tenuous bureaucratic relationship made the personal relationship between bishop and clerk more important. Ultimately, many bishops communicated in terms of friendship with their administrators, who responded with expressions of devotion. Michael Burger's study brings together ecclesiastical, social, legal and cultural history, producing the first synoptic study of thirteenth-century English diocesan administration in decades. His research provides an ecclesiastical counterpoint to numerous studies of bastard feudalism in secular contexts"--
Machine generated contents note: Part I. The Problem: 1. Introduction; 2. Dangers of service; Part II. Rewards and Punishments: 3. Benefice for service and for benefit; 4. Security of tenure in benefices; 5. Pensions; 6. Other rewards; 7. Punishment; Part III. Consequences: 8. Patronage hunger; 9. Continuity and discontinuity in administration; 10. Affection and devotion; 11. Conclusions: culture and context.
Includes bibliographical references and index.
Description based on print version record.
Keywords: England -- Church history -- 1066-1485.; Benefices, Ecclesiastical -- England -- History; Church polity; Church discipline; HISTORY / Europe / Great Britain; RELIGION / Christianity / Catholic; Electronic books